Implementation of Good Governance in Indonesia's Defense and Security Sector Reform Facing the Dynamic of Globalization - Kurniawan Budi Prasetyo; Jonni Mahroza; Hikmat Zakky Al-Mubaroq (UNIVERSITAS PGRI YOGYAKARTA, 2023)
National Defense is the function of the state government in dealing with threats from abroad to uphold the sovereignty, safety, and integrity of the Unitary State of the Republic of Indonesia. Responding to global dynamics, it is necessary to have a professional defense and security sector institution and apply the principles of good governance following the ideal function of government. Government functions in defense and security are managed in ideal defense management. The management regulates all potential defenses to face all threats with the principles of good governance (GG, in realizing the ideal defense management in the face of global dynamics is to improve the quality of cyber security institutions, TNI-Polri, and provide broad access for the community to become part of the defense system). from security and defense actors as reserve components. Therefore, it is necessary to increase the implementation of security and defense based on people-centered security and good governance and policies that focus on developing the professionalism of government institutions in the defense and security sector. Keywords: Good governance, The Defense and Security Sector Reform, Dynamics of Globalization